Study of Passenger Awareness and Satisfaction for IRCTC Catering Service and Dairy Products Offered during Train Journey - , Sudarshan M. Patel, Mahendra D. Gurjar, Krunal .C. Kamani, Maulik C. Prajapati, Ashish.K. Makwana (Archives of Current Research International, 2025)
This study investigates passenger awareness, buying behaviour and satisfaction related to IRCTC's catering services, with a specific focus on dairy product consumption during train journeys. Despite IRCTC's extensive food service network, there remains a lack of research on how well passengers are informed about available offerings, particularly newer options like e-catering and branded dairy products. Primary data were collected from 50 passengers across four major railway stations in Gujarat using structured questionnaires. Findings reveal that 96% of passengers were aware of IRCTC’s role in catering, and 70% had knowledge of e-catering services. Awareness of commonly available dairy items like flavoured milk (96%) and lassi (84%) was high, while only 26% and 16% recognized products like shrikhand and dairy sweets, respectively. Moreover, 58% of passengers reported always purchasing dairy products during their journey, with tea/coffee (84%) and flavoured milk (36%) being most preferred. The study highlights a strong engagement with core services but limited awareness and uptake of diverse dairy offerings. The results point to a clear opportunity for IRCTC to enhance communication strategies, improve product visibility, and strengthen dairy integration within its catering system to meet evolving passenger preferences.